Vestibular incisional subperiosteal tunnel access versus coronally advanced flap with connective tissue graft for root coverage of Miller's class I and II gingival recession: A randomized clinical trial - Saeed Sadat Mansouri; Omid Moghaddas; Narjes Torabi; Katayoun Ghafari (Tabriz University of Medical Sciences, 2019)
Background and aims. This study aimed to compare the clinical efficacy of vestibular incisional subperiosteal tunnel access (VISTA) with subepithelial connective tissue graft versus a coronally advanced flap (CAF) with subepithelial connective tissue graft for the treatment of gingival recession defects. Materials and methods. This randomized clinical trial was performed on 24 recession defects that were bilaterally Miller's class I or II in the maxillary canine and premolar area. One quadrant in each patient was selected randomly to receive VISTA (test group) or CAF (control group) with connective tissue graft. Clinical parameters measured at baseline and at 3- and 6- month postoperative intervals included recession width (RW), recession depth (RD), keratinized tissue width (KTW), clinical attachment level (CAL) and probing depth (PD). Results. Healing was uneventful in both the test and control groups. At the 6-month follow-up, there was a significant decrease in RD, RW and CAL and an increase in KTW in both the test and control groups. The PD remained unchanged. At 3 and 6 months, no statistically significant differences were found between VISTA and CAF for root coverage and clinical attachment gain. Mean root coverage (MRC) was 70.69% and 67.22% in the test and control group, respectively. VISTA demonstrated higher frequency of complete root coverage (CRC) compared to CAF: 50% vs. 33% (P<0.05). The mean KTW was 2.4±0.7 mm at the test and 2.7±0.8 mm at the control sites (P>0.05) Conclusion. VISTA, as a minimally invasive approach, can enhance root coverage, KTW and clinical attachment gain; therefore, it can be used as a substitute for CAF with connective tissue graft as a gold standard for root coverage.